Parametric Lagrangian dual for the binary quadratic programming problem - Xia, Yong; Xing, Wenxun (Journal of global optimization, 2015)
Based on a difference between convex decomposition of the Lagrangian function, we propose and study a family of parametric Lagrangian dual for the binary quadratic program. Then we show they improve several lower bounds in recent literature.